Study of Morphology and Growth of Alocasia spp. from Papua, Indonesia - Daawia Daawia; Juang Gema Kartika; krisantini krisantini; Megayani Sri Rahayu; Ni Putu Sri Asih; Deden D. Matra; Bambang Suhartawan (Hayati Journal of Biosciences)
Alocasia is a genus of perennial, flowering plants from Araceae, native to tropical and subtropical Asia and eastern Australia. The corms of some Alocasia species are edible, but many Alocasia species are cultivated as ornamentals. Despite the rich biodiversity of Alocasia, there have been limited studies on the morphology and anatomy of these genera. Our study aimed to describe the morphology and growth patterns of two Alocasia species found in Papua, one of the remote regions in Indonesia, A. brancifolia and A. lauterbachiana. The existence of A. lauterbachiana in Papua has never been reported before. The two Alocasia species can be distinguished by their distinct leaf shapes and colors. Alocasia brancifolia has pinnatifid leaves, while A. lauterbachiana has serrated leaves. The leaf of A. brancifolia is thin and predominantly green with faint spots, while the petioles exhibit stripes of brown and green, whereas A. lauterbachiana leaves  are thicker and have darker green and reddish color. Due to their attractive leaf shape and colors, both species have the potential to be developed as ornamental potted plants. In terms of growth, A. lauterbachiana exhibited faster growth than A. brancifolia. However, A. brancifolia demonstrated a 50% increase in multiplication over the 16-week study period, while A. lauterbachiana primarily grew taller and larger. This information could prove valuable for future studies to optimize the growth and cultivation techniques of the two Alocasia species for commercial purposes, particularly ornamental foliage plants.